DEVELOPING MANAGEMENT INFORMATION SYSTEM OF PHARMACY WAREHOUSE STOCK (Case Study in RSUD BUDHI ASIH Cawang – Jakarta) - Hamdi, Agus; Saidah, Siti (Universitas Gunadarma, 2008)
RSUD Budhi Asih is a government owned hospital. Their daily activities are to provide medical services. In order to provide fast information services to the patients, computer support that is connected to a networks is required. However, the computer networks have not been used for medicine’s inventory system. Hence, in this research, the development of medicine’s inventory system is developed. The present system of medicine’s inventory relies on stand alone PC so that validation of the quantity, validation of vendor selection and report validation are still taken care manually. With the availability of the new system, data processing for medicine information in the warehouse and satellite warehouse as well as request for medicine from the pharmacy will be fast and easy.Keyword(s) : System, Medicine, Main warehouseSubject Description : K.6.Management of Computing and Information Systems | K.6.1.Project and People Management | System Analysis and Design